Multiobjective Evaluation of Configurations for Hybrid Electric Bus Equipped With Hybrid Energy Storage System Based on Optimal Energy Management Strategy - Kegang Zhao; Yelin Xie; Kunyang He; Zhihao Liang; Yanwei Liu (IET Electrical Systems in Transportation)
For hybrid buses equipped with hybrid energy storage systems, it is crucial to thoroughly evaluate and analyze the potential of different hybrid configurations in order to select an appropriate powertrain configuration for subsequent development. Currently, due to the low efficiency of energy management systems’ multiobjective weighting algorithm and the comparison of different configuration performance under specific component parameters, it is difficult to fully demonstrate the performance potential of configurations. To solve the above problems, multiple allowable component parameter schemes need to be considered. This article introduces a multiobjective evaluation method for hybrid powertrain configurations based on the nondominated sorting dynamic programming algorithm and employs parameter selection and collaborative energy management strategy optimization to overcome the challenge of large computational volume. Through the multiobjective Pareto front of fuel economy and battery SoH (state of health) changes, an effective comparison and analysis of the performance of two hybrid powertrain configurations were conducted. The results reveal that, for an 18-ton urban bus, under equivalent variations in battery SoH, the power-split configuration demonstrates an average fuel consumption reduction of 10.7% compared to the series-parallel configuration. The comparison results of various parameter configuration combinations indicate that the power-split configuration outperforms the series-parallel configuration in urban driving conditions. The aforementioned conclusions also provide reference for the selection of configuration schemes for similar types of commercial vehicles.